Fludarabine and neurotoxicity in engineered T-cell therapy. Issue 3 (June 2018) - Lowe, Kate; Mackall, Crystal; Norry, Elliot; Amado, Rafael; Jakobsen, Bent; Binder, Gwendolyn
Abstract Adoptive T-cell therapy, incorporating engineered T cell receptors (TCRs) or chimeric antigen receptors (CARs), target tumor antigens with high affinity and specificity. To increase the potency of adoptively transferred T cells, patients are conditioned with lymphodepleting chemotherapy regimens prior to adoptive T-cell transfer (ACT), and data suggest that fludarabine is an important component of an effective regimen. In a recent clinical trial using CAR-T cells engineered to target the CD19 B-cell antigen to treat acute lymphoblastic leukemia, JCAR-015 (NCT02535364), two patient deaths due to cerebral edema led to trial suspension. The lymphodepleting agent fludarabine was suggested as the causative agent, in part due to its known association with neurotoxicity and its ability to induce greater potency. In a similar CAR-T study also incorporating fludarabine in the preconditioning regimen, ZUMA-1 (NCT02348216), one patient died of cerebral edema. However, subsequent deaths in the JCAR-015 study after removal of fludarabine and improved understanding behind the mechanisms of CAR-T-related encephalopathy syndrome (CRES) indicate that fludarabine is not the primary causative agent of cerebral edema and that it can be safely incorporated into the preconditioning regimen for ACT. Since entering clinical use in the late 1980s as a chemotherapy agent, fludarabine and similar analogs have been associated with lethal neurological toxicity, yet the manifestation and timing of symptoms are distinct to those observed recently in ACT. Herein, we review the history of fludarabine development as a chemotherapeutic agent, and discuss the safety of its continued use in preconditioning regimens for ACT.